2016
DOI: 10.1038/srep22277
|View full text |Cite
|
Sign up to set email alerts
|

Few-layer HfS2 transistors

Abstract: HfS2 is the novel transition metal dichalcogenide, which has not been experimentally investigated as the material for electron devices. As per the theoretical calculations, HfS2 has the potential for well-balanced mobility (1,800 cm2/V·s) and bandgap (1.2 eV) and hence it can be a good candidate for realizing low-power devices. In this paper, the fundamental properties of few-layer HfS2 flakes were experimentally evaluated. Micromechanical exfoliation using scotch tape extracted atomically thin HfS2 flakes wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 35 publications
10
107
0
Order By: Relevance
“…Thus, with these 2D materials and their combination in heterostructures, it is possible to fabricate new electronic and optoelectronic devices such as flexible FETs, high-electron-mobility transistors (HEMTs), p-n junctions, alternative thin-film solar cells, or photodetectors, among others [5]. monolayer of TiSe2 [10] and, regarding HfX2 (X = S, Se), thin films of HfS2 [11,12] and HfSe2 [13] have 52 been studied for their potential applications in FETs and phototransistors since it is theoretically 53 predicted that monolayers of Zr and Hf TMDCs may exhibit higher mobility than group VIB ones 54 [14]. In addition to the predicted higher mobility, it has been theoretically foretold that ZrX2 55 monolayer may also exhibit an indirect-to-direct band gap transition tuned by strain [15,16] and even 56 a semiconductor-to-metal phase transition [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with these 2D materials and their combination in heterostructures, it is possible to fabricate new electronic and optoelectronic devices such as flexible FETs, high-electron-mobility transistors (HEMTs), p-n junctions, alternative thin-film solar cells, or photodetectors, among others [5]. monolayer of TiSe2 [10] and, regarding HfX2 (X = S, Se), thin films of HfS2 [11,12] and HfSe2 [13] have 52 been studied for their potential applications in FETs and phototransistors since it is theoretically 53 predicted that monolayers of Zr and Hf TMDCs may exhibit higher mobility than group VIB ones 54 [14]. In addition to the predicted higher mobility, it has been theoretically foretold that ZrX2 55 monolayer may also exhibit an indirect-to-direct band gap transition tuned by strain [15,16] and even 56 a semiconductor-to-metal phase transition [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical calculations323334 have shown that in the family of 2D-TMDCs, several materials, such as ZrS 2 , HfS 2 , HfSe 2 , etc., have a lower semiconducting band-gap (0.7–0.9 eV) and could prove to be well suited for application in SB-DIG FETs. For many of these materials experimental evidences are still absent or very limited3536373839, and even in the theoretical ab-initio calculations there are discrepancies in the computed material properties323334 (with great variations especially in the value of the semiconducting band-gap, depending of the functional used in ab-initio simulations). Based on these theoretical analyses, we modeled a 2D-material, according to the properties presented in Table 1, and studied its potential application as a semiconducting channel in polarity-controllable FETs.…”
Section: Resultsmentioning
confidence: 99%
“…This can be justified by the difference in carrier mobilities, as well as, the use of EQE layers on graphene (Table ). Alternatively, HfS 2 has the potential to replace MoS 2 and WSe 2 due to its theoretically predicted mobility of 1800 cm 2 V −1 s −1 at room temperature, however, practical values are still far from this . The low air stability of TMDs structures is still an issue because the adsorption of surface molecules change the TMDs properties, decreasing carrier mobility, and increasing dark current and response time (generation of carrier traps and defects).…”
Section: Discussionmentioning
confidence: 99%